Diversity of stomata and trichomes in Euphorbia L. - I - Devi, N. Sarojini; Padma, Y.; Narasimhudu, C. L.; Raju, R.R. Venkata (Bangladesh Journal of Plant Taxonomy, 2013)
Foliar epidermal features of 18 species of Euphorbia L. s.l. (Euphorbiaceae) are studied. While the anisocytic and anamocytic stomata are common in herbaceous members (Euphorbia subg. Chamaesyce), the paracytic type is predominant in succulent species (Euphorbia proper). The stomatal types, index and frequency, and the types of trichomes are explored on vegetative as well as floral parts to evaluate their possible taxonomic importance. DOI: http://dx.doi.org/10.3329/bjpt.v20i1.15462 Bangladesh J. Plant Taxon. 20(1): 27-38, 2013 (June)